KEBIJAKAN PEMERINTAH DALAM MENJAGA KETERSEDIAAN CADANGAN NIKEL MELALUI MORATORIUM PEMBANGUNAN SMELTER NIKEL - Muhammad Usama Hanif (Al Qalam Jurnal Ilmiah dan Keagamaan, 2023)
Nickel is a natural resource that Indonesia has in great quantities. Its non-renewable nature requires the best possible management so that the benefits are maximally felt by all Indonesians. The enactment of Law Number 3 of 2020 concerning Mineral and Coal Mining makes it mandatory for miners to carry out domestic refining. In January 2023 there were 111 nickel smelters and there were 97 nickel smelters that used saprolite nickel ore with pyrometallurgical technology. if nickel ore is consumed 450 million tons per year, it is likely to run out of reserves in the near future. This situation is an urgency for the government to issue a moratorium on nickel smelters. The government is given the authority represented by the Minister to issue national policies regarding Minerba governance and the Government is also given the responsibility to establish national policies. This moratorium or stoppage is given to smelters with pyrometallurgical technology that utilizes saprolite type nickel ore because the amount is not balanced with its reserves. This moratorium policy is made to maintain the availability of nickel reserves by considering existing reserves through data from the Ministry of Energy and Mineral Resources and referring to the Law.